Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

FORMULAS

Download as pdf or txt
Download as pdf or txt
You are on page 1of 2

Formulas

Unit 2: Derivative Unit 3: Antiderivative


Derivative of an Algebraic Function Basic Rules
𝑑𝑦 𝑑𝑦 a. ∫ 0𝑑𝑥 = 𝐶
a. = 𝑐 = 𝑓 ′ (𝑥) = 0
𝑑𝑥 𝑑𝑥
𝑑 b. ∫ 𝑑𝑥 = 𝑥 + 𝐶
b. (𝑥 ) = 𝑛𝑥 𝑛−1
𝑛
c. ∫ 𝑐𝑑𝑥 = 𝑐𝑥 + 𝐶
𝑑𝑥
𝑑 𝑥 𝑛+1
c. 𝑥=1 d. ∫ 𝑥 𝑛 𝑑𝑥 = 𝑛+1 + 𝐶
𝑑𝑥
𝑑 𝑑
d. 𝑐. 𝑓(𝑥) = 𝑐 𝑑𝑥 𝑓(𝑥) e. ∫ 𝑐𝑓(𝑥)𝑑𝑥 = 𝑐 ∫ 𝑓(𝑥) + 𝐶
𝑑𝑥
𝑑 𝑑 𝑑 f. ∫[𝑓(𝑥) ± 𝑔(𝑥)]𝑑𝑥 = ∫ 𝑓(𝑥)𝑑𝑥 ±
e. [𝑓(𝑥) ± 𝑔(𝑥)] = 𝑓(𝑥) ± 𝑑𝑥 𝑔(𝑥)
𝑑𝑥 𝑑𝑥 ∫ 𝑔(𝑥) 𝑑𝑥
𝑑 𝑑 1 𝑎𝑛𝑥
f. [𝑓(𝑥). 𝑔(𝑥)] = 𝑓(𝑥) 𝑔(𝑥) + g. ∫ 𝑎𝑛𝑥 𝑑𝑥 = 𝑛 . ln 𝑎 + 𝐶
𝑑𝑥 𝑑𝑥
𝑑 1
𝑔(𝑥) 𝑑𝑥 𝑓(𝑥) h. ∫ 𝑒 𝑎𝑥 𝑑𝑥 = 𝑎 . 𝑒 𝑎𝑥 + 𝐶
𝑑 𝑑
𝑑 𝑓(𝑥) 𝑔(𝑥) 𝑓(𝑥)−𝑓(𝑥) 𝑔(𝑥)
𝑑𝑥 𝑑𝑥
g. [ ]= Rules for Trigonometric Function
𝑑𝑥 𝑔(𝑥) [𝑔(𝑥)]2
𝑑𝑦 𝑑 𝑑 a. ∫ cos 𝑥 𝑑𝑥 = sin 𝑥 + 𝐶
h. = 𝑑𝑥 𝑓(𝑥). 𝑑𝑥 𝑔(𝑥) or 𝑦 ′ =
𝑑𝑥

b. ∫ sin 𝑥 𝑑𝑥 = − cos 𝑥 + 𝐶
𝑓 (𝑔(𝑥)). 𝑔′(𝑥) c. ∫ 𝑠𝑒𝑐 2 𝑥 𝑑𝑥 = tan 𝑥 + 𝐶
Derivative of Trigonometric Function d. ∫ csc 𝑥 cot 𝑥 𝑑𝑥 = − csc 𝑥 + 𝐶
e. ∫ sec 𝑥 tan 𝑥 𝑑𝑥 = sec 𝑥 + 𝐶
a.
𝑑
sin 𝑥 = cos 𝑥 f. ∫ 𝑐𝑠𝑐 2 𝑥 𝑑𝑥 = − cot 𝑥 + 𝐶
𝑑𝑥
𝑑
b. cos 𝑥 = − sin 𝑥 Integration by Substitution
𝑑𝑥
c.
𝑑
tan 𝑥 = 𝑠𝑒𝑐 2 𝑥 ∫ 𝑓(𝑔(𝑥))𝑔′ (𝑥)𝑑𝑥 or
𝑑𝑥
𝑑
d. csc 𝑥 = − csc 𝑥 cot 𝑥 ∫ 𝑓(𝑢)𝑑𝑢
𝑑𝑥
𝑑
e. sec 𝑥 = sec 𝑥 tan 𝑥 Integration by using substitution and table of
𝑑𝑥
𝑑 integrals
f. cot 𝑥 = − 𝑐𝑠𝑐 2 𝑥 a. Power of 𝒙
𝑑𝑥
𝑢𝑛+1
1. ∫ 𝑢𝑛 𝑑𝑢 = + 𝐶 where 𝑛 ≠ −1
Derivative of an Exponential Function 𝑛+1
1 −1
2. ∫ 𝑢 𝑑𝑢 = ∫ 𝑢 𝑑𝑢 = ln(𝑢) + 𝐶
𝑑 𝑑
a. 𝑎 𝑥 = 𝑎 𝑥 ln 𝑎 𝑑𝑥 𝑥
𝑑𝑥
𝑑 𝑑 b. Exponential and Logarithmic Function
b. 𝑒 𝑥 = 𝑒 𝑥 𝑑𝑥 𝑥
𝑑𝑥 1. ∫ 𝑒 𝑢 𝑑𝑢 = 𝑒 𝑢 + 𝐶
𝑏𝑢
Derivative of Logarithmic Function 2. ∫ 𝑏 𝑢 𝑑𝑢 = ln 𝑏 + 𝐶
3. ∫ ln 𝑢 𝑑𝑢 = 𝑢 ln 𝑢 − 𝑢 + 𝐶
𝑑 𝑑𝑥
a. log 𝑏 𝑥 = 𝑥 ln 𝑏
𝑑𝑥 c. Trigonometric Function
𝑑 𝑑𝑥
b. ln 𝑥 = 1. ∫ sin 𝑢 𝑑𝑢 = − cos 𝑢 + 𝐶
𝑑𝑥 𝑥
2. ∫ cos 𝑢 𝑑𝑢 = sin 𝑢 + 𝐶
Derivative of Inverse Trigonometric Function 3. ∫ csc 𝑢 𝑑𝑢 = ln | csc 𝑢 − cot 𝑢 | + 𝐶
4. ∫ sec 𝑢 𝑑𝑢 = ln | sec 𝑢 + tan 𝑢 | + 𝐶
𝑑 𝑑𝑥
a. 𝑠𝑖𝑛−1 𝑥 = √1−𝑥 2 5. ∫ tan 𝑢 𝑑𝑢 = ln | sec 𝑢 | + 𝐶
𝑑𝑥
b.
𝑑
𝑐𝑜𝑠 −1 𝑥 = √1−𝑥 2
−𝑑𝑥 6. ∫ cot 𝑢 𝑑𝑢 = ln | sin 𝑢 | + 𝐶
𝑑𝑥
𝑑 𝑑𝑥
c. 𝑡𝑎𝑛−1 𝑥 = 1+𝑥 2 d. Trigonometric Results
𝑑𝑥
d.
𝑑
𝑐𝑠𝑐 −1
𝑥=
−𝑑𝑥 1. ∫ csc 𝑢 cot 𝑢 𝑑𝑢 = − csc 𝑢 + 𝐶
𝑑𝑥 |𝑥|√𝑥 2 −1 2. ∫ sec 𝑢 tan 𝑢 𝑑𝑢 = sec 𝑢 + 𝐶
𝑑 𝑑𝑥
e. 𝑠𝑒𝑐 −1 𝑥 = 3. ∫ 𝑠𝑒𝑐 2 𝑢𝑑𝑢 = tan 𝑢 + 𝐶
𝑑𝑥 |𝑥|√𝑥 2 −1
f.
𝑑
𝑐𝑜𝑡 −1 𝑥 = 1+𝑥 2
−𝑑𝑥 4. ∫ 𝑐𝑠𝑐 2 𝑢𝑑𝑢 = −cot 𝑢 + 𝐶
𝑑𝑥
e. Inverse Trigonometric Function
1. ∫ sin−1 𝑢 𝑑𝑢 = 𝑢 sin−1 𝑢 + √1 − 𝑢2 + 𝐶
2. ∫ csc −1 𝑢 𝑑𝑢 = 𝑢 csc −1 𝑢 + ln |𝑢 + √𝑢2 − 1| +
𝐶
1
3. ∫ tan−1 𝑢 𝑑𝑢 = 𝑢 tan−1 𝑢 − 2 ln( 1 + 𝑢2 ) + 𝐶
4. ∫ cos −1 𝑢 𝑑𝑢 = 𝑢 cos −1 𝑢 − √1 − 𝑢2 + 𝐶
1
5. ∫ cot −1 𝑢 𝑑𝑢 = 𝑢 cot −1 𝑢 + 2 ln( 1 + 𝑢2 ) + 𝐶
6. ∫ sec −1 𝑢 𝑑𝑢 = 𝑢 sec −1 𝑢 − ln |𝑢 + √𝑢2 − 1| + 𝐶

f. Inverse Trigonometric Results


𝑑𝑢 𝑢
1. ∫ √𝑎2 2 = 𝑠𝑖𝑛−1 𝑎 + 𝐶; 𝑎 > 0
−𝑢
𝑑𝑢 1 𝑢
2. ∫ 𝑎2 +𝑢2 = 𝑎 𝑡𝑎𝑛−1 𝑎 + 𝐶; 𝑎 > 0
𝑑𝑢 1 |𝑢|
3. ∫ = 𝑎 𝑠𝑒𝑐 −1 + 𝐶; 𝑢 > 𝑎 > 0
𝑢√𝑢2 −𝑎2 𝑎

You might also like